The effect of compensation, Education and Training, and Self-Efficacy on Hotel Sales Marketing Performance in North Sumatera Province Moderated by Constructive Retention - Hasyim (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2022)
The problem in this study is the low loyalty and performance of sales marketing staff at 3-star to 5-star hotels in North Sumatra. The phenomenon that occurs that low hotel sales marketing loyalty is caused by compensation, education and training, and low self-efficacy. This study examines the effect of balance, education and training, and self-efficacy as independent variables and constructive retention as an intervening variable on the sales marketing performance of 3-star to 5-star hotels in North Sumatra. The research findings show a positive and significant effect of compensation, education and training, and self-efficacy on sales marketing performance and constructive retention as intervening variables. The results of this study can be used as a reference for hotel management on how to build the performance of sales marketing employees with constructive retention. Based on hypothesis testing, all hypotheses constructed in this study proved to have a positive and significant effect. The empirical findings also uncovered that the respondents' qualitative answers to the indicators were good, meaning that the indicators used in this study were feasible.